Eco-Spirituality and the Nature of Colonialism in F. Sionil Jose’s The God Stealer - Hammim B. Casan (Randwick International of Social Science Journal, 2022)
Ecocritics argue that everything in the world is interconnected and that humans have a moral obligation to safeguard nature. According to some researchers, human culture and nature are intricately intertwined and impact one another. As a result, this is one of the few studies that looked at the nature of colonialism as described in F. Sionil Jose's The God Stealer. It also looked into the idealization of nature and the rural by building a link between nature and culture. Furthermore, the data revealed that nature plays an important role in many indigenous ceremonies, customs, cultures, and spiritualities. The concept is not to reject the worldly, but to live in harmony with nature. It argues that God's existence is revealed through His creation and creatures. Moreover, the theft of an idol or god in The God Stealer implies disregard for tribal beliefs and traditions. In addition, the character Sam Christie personifies an exploitative colonial force that devalues an idol/god (nature) by turning it into a collectible. The analyses also show that colonialism has caused alterations to traditional tribal ways of living. Thus, it is evident that the nature of colonialism is portrayed in F. Sionil Jose's The God Stealer. Also, An analysis of the eco-feministic approach to discovering masculine colonialism, as well as the socio-political structures, may be studied in order to uncover the themes and sub-themes in F. Sionil Jose’s Literature.